1 answer

(click or scroll down)

## To determine if the equation is in quadratic form, we need to check if it can be written in the form of ax^2 + bx + c = 0, where x represents the variable and a, b, and c are coefficients.

In the given equation v(v - 3) = v^2 + 6, we can simplify it by expanding the left side:

v^2 - 3v = v^2 + 6.

By rearranging the terms, we get:

v^2 - v^2 - 3v = 6.

Simplifying further:

-3v = 6.

Dividing both sides by -3, we have:

v = -2.

Since we obtained a value for v rather than a quadratic equation of the form ax^2 + bx + c = 0, we can confirm that the given equation is not in quadratic form.

For further understanding on quadratic forms and how to solve them, you can refer to the link provided: http://www.wtamu.edu/academic/anns/mps/math/mathlab/col_algebra/col_alg_tut20_quadform.htm